Are you understanding what I am saying? The critical importance of communication competency in epidemiology - Alison G. Abraham; Alison G. Abraham; WayWay M. Hlaing (Frontiers in Public Health)
There are myriad examples of poor communication by public health scientists and researchers that have resulted in lasting harm to individuals, communities, the field of epidemiology, and the broader field of public health. These examples underscore that science messages hinge not only on their merit alone but also on how effectively we communicate them. Here, we highlight the strong consensus in the epidemiology educational literature that epidemiology students should be trained to communicate effectively, specifically with the general public. This allows the public access to critical information that could affect their well-being. Most epidemiology programs in academia do not focus on the skills needed to translate scientific evidence and its uncertainty into a comprehensible and culturally appropriate message to the diverse public composed of varying race/ethnicities as well as varying health and numerical literacy levels. We provide guidance on which specific communication skills may be most important for epidemiologists facing the growing health misinformation and disinformation epidemic. We also describe what a communication-focused curriculum might look like, given that communication skills cannot be learned solely through traditional coursework. Lastly, we address barriers that have prevented communication skills from being meaningfully incorporated in epidemiology curricula.